PENGARUH STATUS GIZI TERHADAP KADAR YODIUM URIN SETELAH PEMBERIAN KAPSUL YODIUM PADA ANAK SEKOLAH DASAR DI DAERAH GONDOK ENDEMIK - Sri Prihatini; Syarifudin Latinulu (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2002)
EFFECT OF NUTRITIONAL STATUS ON IODINE URINE LEVEL AFTER IODIZED OIL SUPPLEMENTATION OF SCHOOL CHILDREN IN ENDEMIC GOITRE AREA.Background: One of the government strategic to prevent iodine deficiency disorders (IDD) is oral iodized oil supplementation, since it has economic and many practical advantages over injections. However there are high variations in efficacy and the average duration of protection often ranging from 6 month to 1 year. Many factors that influence the absorption and retention of oral iodized oil such  as the nutritional status, the presence of intestinal parasites, sex and age of the subject.Objectives: The objective of this research was to study the effect of nutritional status on iodine urin level after iodized oil supplementation.Methods: The study design was cohort prospective with nutritional status as risk factor. Research population was elementary school children aged 6-10 years in three villages of Cidahu subdistrict, West Java Province.Results: The result showed that average amount of iodine excreted by urine for three days was higher (27%) in group of moderate malnutrition compared with good nutrition group (25,5%), but this was not significantly different (p>0,05). Median level of iodine urine after 6 month showed which was 87 ug/l for moderate malnutrition group and 110 ug/l for good nutrition group, and this was significantly different (p<0,05). With urine adequacy level of 100 ug/l, after 6 month, 66% children with moderate malnutrition and 29,3% with good nutrition have mild deficiency (P<0,05).Conclusions: The research concluded that average amount of iodine excreted in urine for three days was higher in group of moderate malnutrition compared with good nutrition group but his was not significantly different. Children with moderate malnutrition have greater iodine deficiency risk than good nutrition after 6 months.Keywords: nutritional status, oral iodized oil, iodine urine level